Analisis Disproporsional Beban Kerja Panitia Pemungutan Suara Nagari Air Bangis Menggunakan Studi Integritas - Afrilla, Ade; Irmayani, Tengku; Fauzan, Indra (Universitas Medan Area, 2024)
The working area of PPS Nagari Air Bangis is the same as the PPK Kecamatan Sungai Beremas, with a coverage area of 440.48 Km2, which has an island area and is difficult to access. This phenomenon is caused by the Sungai Beremas Sub-district, which only has 1 (one) village called Nagari, namely Air Bangis. This condition causes the large burden of simultaneous elections to make a disproportionate (excessive) workload for PPS members of Nagari Air Bangis because it has 81 polling stations and 19,252 DPT. Koesomowidjojo's workload theory (2021) and Hart & Staveland (1988) are used to answer these problems. The integrity of its implementation is based on the 11 principles of Election Article 3 of Law 7/2017 concerning Elections. This research uses an exploratory qualitative method. Data and facts are collected comprehensively through in-depth interviews and observations. Data analysis was done using data collection, condensation, presentation, and conclusion drawing. This study concludes that PPS Nagari Air Bangis members have a disproportional workload influenced by internal and external factors. External factors include excessive task load, large work areas, and non-ideal work organization. Internal factors include the organizer's innate physical (somatic) and mental (psychic) working state due to external loads. Although there is a disproportionate workload of PPS Nagari Air Bangis members, this does not cause violations of election integrity, which results in re-election (PSU) or criminal acts.